New features in EXPO2007, a program for crystal structure resolution from powder data - Altomare, Angela (Array, 2008)
Summary: New approaches have been introduced in the EXPO2007 program aiming at making easier and straightforward the ab initio crystal structure solution from powder diffraction data. Improvements in space group determination, powder pattern decomposition, least squares Fourier recycling, interpretation of the electron density map have been developed. To manage organic crystal structures a new strategy in direct-space, combining Direct Methods and Simulated Annealing approaches, has been implemented